Measurement of the transverse momentum distribution of Z/γ∗ bosons in proton–proton collisions at √s = 7 TeV with the ATLAS detector - Anduaga, Xabier Sebastián (2011)
A measurement of the Z/γ∗ transverse momentum (pZT) distribution in proton–proton collisions at √s = 7 TeV is presented using Z/γ∗ → e+e- and Z/γ∗ → μ+μ- decays collected with the ATLAS detector in data sets with integrated luminosities of 35 pb-1 and 40 pb-1, respectively. The normalized differential cross sections are measured separately for electron and muon decay channels as well as for their combination up to pZT of 350 GeV for invariant dilepton masses 66 GeV < mℓℓ < 116 GeV. The measurement is compared to predictions of perturbative QCD and various event generators. The prediction of resummed QCD combined with fixed order perturbative QCD is found to be in good agreement with the data.